Tetrazine Chelate Ligands Bridging Two [Ru(acac)2] Fragments: Mixed Valency and Radical Complex Formation - Kaim, Wolfgang; Löw, Isabell; Ringenberg, Mark R.; Schwederski, Brigitte; Filippou, Vasileios; Fiedler, Jan (Zeitschrift für anorganische und allgemeine Chemie (1950), 2022)
Using bis(3‐methyl‐2‐pyridyl)‐1,2,4,5‐tetrazine 1, 3‐(2‐pyrimidyl)‐6‐methyl‐1,2,4,5‐tetrazine 2 and bis(2‐pyrimidyl)‐1,2,4,5‐tetrazine=bmtz as ligands, the complexes 3=[Ru(acac)2(1)], 4={[Ru(acac)2]2(1)], 5={[Ru(acac)2]2(bmtz)], and 6={[Ru(acac)2]2(2)] were prepared and identified by structure analysis of crystallized material. The one‐electron oxidized form 6(PF6) was also studied structurally, suggesting a Class II mixed‐valent situation. The neutral dinuclear systems exhibit two reversible oxidation processes with comproportionation constants 109.2<Kc<1014.1 and one reduction which were analyzed UV/vis/NIR and EPR spectroscopically. Oxidation produces largely metal‐based mixed‐valent cations with very weak intervalence absorptions in the near IR whereas the electron uptake occurs at the tetrazine acceptor.